INOVASI LAYANAN DASAR PEMERINTAH DALAM AKSELERASI ANGKA PARTISIPASI SEKOLAH DI KOTA SERANG - Prastio, Luki Oka; Khanifah, Laeli Nur (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This research is motivated by the decline in the school participation rate (APS) in Serang City, which based on data of 1,157 children in 2024 increased drastically from the previous year. This problem is caused by economic conditions, bullying, low motivation of children to attend school, and internal stigma of families, as well as other external factors. The surge in the number of children not attending school has encouraged the government to accelerate efforts to encourage school participation through the Aje Kendor Program. The purpose of this study is to capture how the government's efforts through the Aje Kendor Program are able to return children not attending school, which is analyzed using the theory of public service innovation. This research uses qualitative methods, with a research focus on elementary and junior high school education levels. Data collection was carried out through observation, interviews, documentation and literature studies. Data validation techniques were carried out through source triangulation. The results of the study show that the Aje Kendor program is quite optimal based on 1) Organizational and process innovation, there has been cross-sectoral collaboration that encourages the achievement of program objectives, through comprehensive and rapid process innovation using integrated technology from the grassroots level to ensure targeting. 2) Product innovation is manifested in program flexibility, which is able to assess the target's conditions in terms of time, territory, interests, needs, and even psychological well-being. 3) Paradigm innovation is evident in the participation and contribution of all actors in supporting program implementation, including budgeting, regulations, and implementation. The government's commitment is also evident in the program's inclusion in regional development plans.